301 IS IT WORTH USING MESH FOR THE TREATMENT OF GIANT HIATAL HERNIA? A SYSTEMATIC REVIEW AND META-ANALYSIS. (14th September 2020) - de Campos, V; Palacio, D; Glina, F; Tustumi, F; Bernardo, W; de Sousa, A
Abstract:  : The use of mesh associated with cruroplasty is still controversial in giant hernias, due to possible complications of the prosthesis reported in the literature, such as infection, chest migration, shrinkage, esophageal and aortic erosion, stenosis and obstruction. This systematic review and meta-analysis aimed to compare the use or not of mesh as a reinforcement in the laparoscopic repair of giant hernias and to determine which technique has the best results in recurrence and complication rates. Methods: A search was conducted using databases and included prospective and randomized studies. The studies should include patients with giant hernias who have undergone laparoscopic treatment comparatively analyzed between cruroplasty and suture associated with prosthetic reinforcement. Results: Of the 768 articles analyzed, 8 were selected for systematic review, and 7 were included in the meta-analysis. The meta-analysis showed no statistically significant differences in favor of any of the intervention methods (mesh versus suture cruroplasty) for the different outcomes evaluated: recurrence (RD -0.06, CI [−0.13, 0.01], I2 22%, p 0.27); postoperative complications (RD 0.04, CI [−0.01, 0.9], I2 5%, p 0.30); deaths (RD -0.01, CI [−0.04, 0.02], I2 0%, p 74); intraoperative complications (RD -0.03, CI [−0.07, 0.1]); reoperation (RD -0.04, CI [− 0.10, 0.02], p 0.14). Conclusion: There is no evidence supporting that routine mesh reinforcement in laparoscopic repair of giant hernias decreases recurrence and other complications. Systematic review registration number at PROSPERO: CRD42019147468.